Efficacy and safety of oral antiviral therapy medications in the treatment of moderate and severe cases of COVID-19. Results of a comparative retrospective observational study - A. U. Sabitov; E. P. Tikhonova; E. V. Esaulenko; P. L. Kuznetsov; A. A. Sharova; T. A. Yelistratova; Yu. S. Kalinina; I. V. Andreeva; V. V. Basina; E. V. Oleinichenko; A. S. Edin (Антибиотики и Химиотерапия, 2024)
The aim of the study was to compare the clinical efficacy and safety of two antiviral therapy medications that suppress viral replication (viral RNA polymerase inhibitors) in the treatment of patients with COVID-19: favipiravir and riamilovir.Material and methods. Clinical efficacy and safety were assessed based on a retrospective study of 1071 patients, including 561 patients who received favipiravir and 510 patients who received riamilovir.Results. A statistically significant reduction in the duration of symptoms and average hospital days was recorded among patients who received ramilovir in both moderate and severe forms of the disease compared with the group that received favipiravir. Inflammatory markers (CRP, fibrinogen) decreased faster in the riamilovir group.Conclusion. Riamilovir has demonstrated higher levels of clinical efficacy and safety in the treatment of COVID-19 compared to favipiravir.